Jean-Michel Grandmont - A Forthcoming Mind - Laurent Linnemer; Michael Visser (Center for Economic Studies and ifo Institute (CESifo), 2018)
This profile of Jean-Michel Grandmont is based on several interviews we had with him between September 2016 and April 2017. The interviews took place at our CREST offices, located at that time in Malakoff, just south of Paris. The objective of the profile is twofold. First, we trace the career of this highly influential mathematical economist who made seminal contributions to the fields of monetary economics, temporary equilibrium, business cycle theory, and aggregation of individual behavior. Second, we show how Grandmont and his colleagues contributed to changing the French landscape of economic research.
Keywords: B31; D50; D70; E30; 330; general equilibrium; money; nonlinear dynamics